Ypres. Eglise St. Martin - St. Martin's Church (01), GP036521 - Auteur inconnu (Wikimedia Commons)
Carte postale ancienne issue de Wikimedia Commons. Titre: Ypres. Eglise St. Martin - St. Martin's Church (01), GP036521. Title Ypres. Eglise St. Martin - St. Martin's Church [01] Date [date de publication inconnu] Publisher Bruxelles: Thill Uniform title Ieper. Gebouwen. Kerken en kapellen Series Belgique. Province de Flandre occidentale. Cartes postales Belgium. Province of West-Flanders. Postcards België. Provincie West-Vlaanderen. Prentkaarten Genre Post cards Extent 1 kaart / postcard Graphic Brown Language French Additional info General note: Ieper. Sint-Martinuskerk [Sint-Martinuskathedraal / Sint-Maartenskathedraal / Sint-Maertens Hoofdkerk / Sint-Maartens Hoofdkerk] General note: Titelgegevens ontleend aan prentkaart Source Library Catalog Source ID lbsn9992400542601471
Droits : Licence Public domain via Wikimedia Commons
Keywords: carte postale; image; patrimoine; histoire locale; wikimedia commons; église; Carte postale